The introduction of Bantu education and the question of resistance, co-operation, non-collaboration or defiance?: the struggle for African schooling with special reference to Cape Town, 1945-1960 - Cameron, Michael James (School of Education, 2024)
The purpose of the Bantu Education Act was to extend the state's direct political control over African communities: African resistance modified this control and shaped the implementation of Bantu Education. Through the centralization of the administration and the financing of African schooling the state was able to accommodate an increasing demand for schooling at a reduced cost per pupil. Control of these schools was exercised through inspectors and through statutory School Committees and School Boards. A secondary purpose of Bantu Education was to provide suitably skilled and co-operative workers to meet the needs of a growing industrial economy. The major national resistance to state control came from the A.N.C. in the form of the Bantu Education Campaign. This plan that parents should withdraw their children from state schools from 1 April 1955 received wide support in the East Rand and Eastern Cape areas. African opposition to the intervention by the state also influenced the outcome of Bantu Education - it defined the limits of the state's control and it increased the need to supply an acceptably academic education. A case study of the implementation of Bantu Education in Cape Town illustrates the above contentions. Not only were School Boards and Committees used to regulate the schools, also the selective opening of schools in the new official location and closing of other schools in “non-African” areas point to Bantu Education being used as a lever to resettle Africans. Economically the expansion of African schooling coincided with a rapid growth in Cape Town's industry but there was no simple correspondence between the two. The response to the A.N.C call to withdraw pupils from schools in Cape Town was limited not because of the absence of traditions of resistance in the City but because of divisions between resistance movements. The defiant proposal of the A.N.C was condemned by the Cape African Teachers' Association (and the Unity Movement) as shifting the burden of the struggle onto the children. The conflict between the two bodies concerned more than tactical differences since they refused to co-operate even when their tactics were the same. (e.g. to boycott School Boards and School Committees). The failure to unite resistance to Bantu Education in Cape Town arose essentially from the fact that the local A.N.C. and C.A.T.A. branches were linked to opposing movements for national liberation, viz. The Congress Alliance and the Non-European Unity Movement respectively. The latter body called on Africans not to collaborate by participating on School Boards or voting for School Committees.